Inter-municipal cooperation in Serbia - opportunities and practical scope - Stančetić, Veran (Serbian political thought, 2023)
European experiences indicate numerous forms of inter-municipal cooperation, ranging from simpler forms aimed at more efficient and rational management (such as joint local public enterprises or shared administrations) to integrative forms where inter-municipal unions are formed, possessing legal subjectivity and their own governance structure (union assembly, president, budget, etc.). The main purpose of such cooperation models is the collective decision-making on public policies and jointly management of territorial development encompassing multiple municipalities. This can serve as an alternative to formal regionalization and regional self-governance, particularly in cases where the regional level of governance is underdeveloped.These experiences can be valuable for Serbia, considering that formal decentralization has not been embraced as an option by the authorities thus far, despite the need for regional governance, especially in the context of European integration, balanced regional development, and further democratization. The legislator in Serbia has not yet anticipated this kind of complex or integrative inter-municipal cooperation. However, in recent years, there has been a promotion of the idea of inter-municipal cooperation (in simpler forms), which is reflected in the current Law on Local Self-Government, as well as in the initial financial incentives. The paper initially presents the challenges of modern governance and reform directions, as well as the significance and practical scope of inter-municipal cooperation in European countries. Subsequently, the formal-legal possibilities for municipalities in Serbia to cooperate are examined, followed by practical implications and possibilities (based on European practices) that can be developed in the future.
Keywords: municipalities, cities, inter-municipal cooperation, regional governance, regional decentralization, democratization, regional development, European Union